HUBUNGAN AKTIVITAS FISIK DENGAN TEKANAN DARAH PADA LANSIA YANG MENDERITA HIPERTENSI - Devi Afriza; Ari Pristiana Dewi; Yufitriana Amir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries countinously for more than one periode. Efforts that can be made for hypertension sufferers can be done with medication and implementing a healthy lifestyle one of is by doing physical activity. Active physical activity, as well as the frequency and length of time used properly and correctly can help lower blood pressure. The risk of hypertension will be lower if someone does physical activity. This study aims to determine the relationship of physical activity with blood pressure in elderly who suffer from hypertension. The research design was descriptive correlation with cross sectional approach. The sampling methode was use methode purposive sampling, with 84 respondents of sample based on the inclusion criteria. The results found that the samples between 60-69 years old were 85.7%, female was 53.6%, senior high school graduates was 36.9%, houseworks was 28.6%. The category for physiscal activity is moderate physical activity was 39.3%, the category for blood pressure is hangover hypertension one was 50.0%. Chi square result showed p value (0,00) < α (0,05). It can be concluded that there was a relationship between physical activity with blood pressure in the elderly suffering from hypertension. The more often the elderly carry out physical activity the more it can be reduce hypertension in these elderly. It is expected that nurses in Puskesmas can provide more promotive efforts by conducting health education about benefits of physical activity to reduce hypertension. Keyword : Physical activity, blood pressure, elderly